Impacts of Droughts and Floods on Agricultural Productivity in New Zealand as Measured from Space - Elodie Blanc; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2022)
This study estimates the impact of excess precipitation (or the absence of rainfall) on productivity of agricultural land parcels in New Zealand. This type of post-disaster damage assessments aims to allow for quantification of disaster damage when on-the-ground assessment of damage is too costly or too difficult to conduct. It can also serve as a retroactive data collection tool for disaster loss databases where data collection did not happen at the time of the event. To this end, we use satellite-derived observations of terrestrial vegetation (the Enhanced Vegetation Index – EVI) over the growing season. We pair this data at the land parcel level identifying five land use types (three types of pasture, and annual and perennial crops) with precipitation records, which we use to identify both excessively dry and excessively wet episodes. Using regression analyses, we then examine whether these episodes of excess precipitation had any observable impact on agricultural productivity. Overall, we find statistically significant declines in agricultural productivity that is associated with both floods and droughts. The average impact of these events, averaged over the affected parcels, however, is not very large; usually less than 1%, but quite different across years and across regions. This average hides a heterogeneity of impacts, with some parcels experiencing a much more significant decline in the EVI.
Keywords: Q15; Q54; C23; 330; satellite-derived data; crop productivity; drought; flood